2022
DOI: 10.1101/2022.11.11.22282224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wastewater as a back door to serology?

Abstract: Wastewater surveillance is a powerful tool for monitoring the prevalence of infectious disease in urban populations, with predictive value for upcoming increases in cases and hospitalizations. The approach primarily used in disease surveillance has been to measure the number of viral copies detected in wastewater for a study area of known population, and systems for wastewater monitoring have been put in place worldwide during the SARS-CoV-2 pandemic. However, the potential to measure other biomarkers such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…15 More recently, measurement of specific Igs in wastewater was proposed as a window for community serology and an ELISA method was developed in the context of COVID surveillance. 18 Igs are large heterodimeric glycoproteins composed of two heavy and two light chains, each of which is a combination of different variable and constant domains encoded by 176 genes. There are five Ig isotypes named based on their α, Δ, ϵ, γ, and μ heavy chains (IgA, IgD, IgE, IgG, and IgM, respectively), each containing one of the two classes of light chains (κ and λ).…”
Section: Albumins As Livestock Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…15 More recently, measurement of specific Igs in wastewater was proposed as a window for community serology and an ELISA method was developed in the context of COVID surveillance. 18 Igs are large heterodimeric glycoproteins composed of two heavy and two light chains, each of which is a combination of different variable and constant domains encoded by 176 genes. There are five Ig isotypes named based on their α, Δ, ϵ, γ, and μ heavy chains (IgA, IgD, IgE, IgG, and IgM, respectively), each containing one of the two classes of light chains (κ and λ).…”
Section: Albumins As Livestock Industrymentioning
confidence: 99%
“…16 More recently, using ELISA analyses, quantitation of human immunoglobulins A and G in wastewater was reported and proposed as a tool for community serology. 18 Besides these works, most sewage proteomic studies have focused on the characterization of the microbiome in either sludge 19 or wastewater, 16,20 and the information on other human, animal, or vegetal proteins remains scarce at best.…”
Section: Introductionmentioning
confidence: 99%
“…80,81 Other analytical techniques that warrant further investigation include loop-mediated isothermal amplification (LAMP) and helicase-dependent amplification (HDA) which can return results in shorter time frames and have been implemented on lateral flow test strips in clinical and environmental settings. [82][83][84] More novel techniques that could become relevant include mass spectrometry for the detection of proteins relevant to specific pathogens 85 , enzyme-linked immunosorbent assays (ELISA) to detect specific antibodies 86 , or clustered regularly interspaced short palindromic repeats (CRISPR)-based diagnostic assays. 87,88 In contrast to targeted diagnostic techniques (e.g., PCR, LAMP, CRISPR), next generation sequencing (NGS) can offer semi-targeted or even untargeted analytical capabilities.…”
Section: Aircraft Wastewater Analytical Approachesmentioning
confidence: 99%
“…The demonstration of antibodies in wastewater is a potential first step towards tracking community immunity levels, opening the possibility of defining immune protection thresholds for a given pathogen and monitoring the efficacy of a mucosal vaccine campaign. Protein mass spectrometry has identified significant amounts of human Ig chain peptides in wastewater (18) and a preprint by Agan et al (19) found that wastewater collected at both building- and WRRF-scales contained SARS-CoV-2 specific IgG and IgA antibodies by enzyme-linked immunosorbent assay (ELISA). However, the extent of intact and functional human antibody pools in urban wastewaters remains unclear.…”
Section: Introductionmentioning
confidence: 99%